La civilisation internationale des moeurs : éléments pour une sociologie de l'idéalisme structurel dans les relations internationales - Sindjoun, Luc (Études internationales, 1996)
Human rights have been seen as basic to the ethical distinctiveness and legitimization of states. They also contribute to the international culture of state moral standards. Interdependence between states is based on a minimum of shared values or accepted rules, including human rights, which symbolically constitute a universe of constraints. The codification of human rights through the International Covenant on Civil and Political Rights and Africa's experience in the area of international ethics support the hypothesis of an international culture of moral standards.